2014
DOI: 10.5709/ce.1897-9254.153
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Risk Management Decision of Small and Medium Scale Enterprises in Ghana

Abstract: This research seeks to study the factors that enhance or preclude owners of SMEs in Ghana in making risk management decisions. The study was conducted with managers of SMEs in four regions in Ghana. The researchers adopted a quantitative approach and employed STATA 10 and SPSS version 20 in the analysis. Stratified and simple random sampling techniques were used to select the sample units. The probit model was used in the analysis of data. A total of 447 SMEs were sampled for the study, with at least 111 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
(4 reference statements)
2
12
0
Order By: Relevance
“…This research employed Ordinary Least Squared (OLS) to examine the association between the independent variables; including financial, management, marketing, technological, and government policy and regulations and the dependent variables; namely SMEs performance. The results show that all independent factors had statistically significant effect on SMEs performance, this results is consistent with previous studies results (Bouazza et al, 2015;Amwele, 2013;Abotsi et al, 2014). In general, it can be concluded that the financial factors, management factors, marketing factors, technological factors, and government policy and regulations have maintained positive statistically significant effect on SMEs performance.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This research employed Ordinary Least Squared (OLS) to examine the association between the independent variables; including financial, management, marketing, technological, and government policy and regulations and the dependent variables; namely SMEs performance. The results show that all independent factors had statistically significant effect on SMEs performance, this results is consistent with previous studies results (Bouazza et al, 2015;Amwele, 2013;Abotsi et al, 2014). In general, it can be concluded that the financial factors, management factors, marketing factors, technological factors, and government policy and regulations have maintained positive statistically significant effect on SMEs performance.…”
Section: Resultssupporting
confidence: 91%
“…SMEs are accounted for 90% of the worlds enterprises and provide employment opportunities of about 50% of the organized employment (Word Bank Group, 2017). Researchers concentrated on investigating different factors influencing the performance of SMEs in developed and developing countries (Margaretha & Supartika, 2016;Farrokh et al, 2016;Abotsi et al, 2014;Kinyua, 2014;Amwele, 2013). In Jordan, SMEs form a pivotal role in production and operation, employment, income generation and innovation to achieve the economic goals for which they were created.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, these ex-ante transaction costs for evaluating small businesses during the supplier selection process have never been quantified, and have never been compared to non-small business suppliers. Additionally, buyers who are obligated to set aside sourcing dollars for small businesses perceive greater transaction costs as a result, a fact which drives buyer behavior to reduce transaction costs by using a simplified source selection method (Abotsi et al, 2014;Edvardsson and Teitsdóttir, 2015;Rocha et al, 2015). Lastly, while a common paradigm is held among buyers that selecting small firms poses additional supplier performance risk (Ivory, 2012) as the final outcome (that is, greater transaction costs to rectify performance problems ex post), we find no extant empirical studies of this postulate.…”
Section: Transaction Cost Economics (Tce)mentioning
confidence: 99%
“…Moreover the International Labor Organization (ILO) (2014) reports that African economic growth rate in 2013 proved too low to generate sufficient employment opportunities for a rapidly growing population, (ILO, 2014). Meanwhile the engine through which the growth objectives of developing countries can be achieved are these firms (Abotsi et al, 2014). Therefore the need to explore the influence of power outages on firm production efficiencies cannot be overemphasized.…”
Section: Introductionmentioning
confidence: 99%